(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article describes the peculiarities of organization of a group learning activity of primary school children at the lessons of Ukrainian language, generalized psychological and pedagogical conditions of formation of self-control skills of pupils in a group activity, and submitted samples of exercises and tasks that can be used by primary school teachers at the lessons of Ukrainian language for organization of group learning activities of children.